Older Adults Automatically Detect Age of Older Adults’ Photographs: A Visual Mismatch Negativity Study - Csizmadia, Petra; Petro, Bela; Kojouharova, Petia; Gaál, Zsófia Anna; Scheiling, Katalin; Nagy, Boglárka; Czigler, István (Frontiers in Human Neuroscience, 2021)
The human face is one of the most frequently used stimuli in vMMN (visual mismatch negativity) research. Previous studies showed that vMMN is sensitive to facial emotions and gender, but investigations of age-related vMMN differences are relatively rare. The aim of this study was to investigate whether the models’ age in photographs were automatically detected, even if the photographs were not parts of the ongoing task. Furthermore, we investigated age-related differences, and the possibility of different sensitivity to photographs of participants’ own versus different ages. We recorded event-related potentials (ERPs) to faces of young and old models in younger (N = 20; 18-30 years) and older groups (N = 20; 60-75 years). The faces appeared around the location of the field of a tracking task. In sequences the young or the old faces were either frequent (standards) or infrequent (deviants). According to the results, a regular sequence of models’ age is automatically registered, and faces violating the models’ age elicited the vMMN component. However, in this study vMMN emerged only in the older group to same age deviants. This finding is explained by the less effective inhibition of irrelevant stimuli in the elderly, and corresponds to own-age bias effect of recognition studies.